Cover Feature: Gas‐Phase Transformation of Fluorinated Benzoporphyrins to Porphyrin‐Embedded Conical Nanocarbons (Chem. Eur. J. 53/2020). Issue 53 (1st September 2020) - Lungerich, Dominik; Hitzenberger, Jakob Felix; Ruppel, Michael; Döpper, Tibor; Witt, Matthias; Ivanović‐Burmazović, Ivana; Görling, Andreas; Jux, Norbert; Drewello, Thomas
Abstract : A conical porphyrin fully embedded in a carbon nanosheet was prepared by collision‐induced dissociation of saddle‐shaped tetraaryltetrabenzoporphyrins, by means of hydrogen fluoride elimination in the mass spectrometer. Supported by density functional theory calculations, mechanistic insights were gained by variation of central metal atoms and fluorophenyl substituents. The structure represents a potential candidate for the growth of porphyrin‐embedded graphene and related structures. More information can be found in the Full Paper by D. Lungerich, N. Jux, T. Drewello, et al. on page 12180 .